Latin America: 2022 - Solari De La Fuente, Luis (2021)
The world is undergoing a process of broad, complex, fast and non-sequential change. Part of this change has been the growing development of the Pacific Ocean Basin, a fact that has enhanced the geostrategic relevance of Latin America as the great bioceanic territory. The region does not have a multinational agenda in this regard. Its public administrations have not been able to solve pressing chronic problems, the solution of which is essential to advance in the indispensable strategic integration for the development of joint actions in the aforementioned Basin. The COVID-19 pandemic has shown the ineffectiveness of our Latin American public administrations controlling it, as an example of what is urgent to correct. Possible solutions are proposed.